In the presence of your majesty!: The management of Manoel Tovar in Espírito Santo (1804-1812) (Ágora Journal, 2021)
When Manoel Vieira da Silva de Albuquerque e Tovar took over the administration of Espírito Santo, between 1804 and 1812, his mission was to continue the project of inserting the captaincy in the logic of development of the Portuguese State, in a context, inaugurated in the last decade of the 18th century, marked by the insertion of academics in the colonial administration posts. The governor's mission was to generate forms of land exploration, based on scientific studies, with the purpose of meeting the demands of the Metropolis, even if this meant disregarding a socioeconomic structure already found in Espírito Santo territory, throughout the colonial centuries, characterized by dynamics trade involving internal supply and the use of coastal cabotage. This article seeks to understand the period of Manoel Tovar in Espírito Santo, considering the instructions presented by the Crown and the positioning of local elites regarding the direction of the governor's administration. Therefore, the research involves a qualitative analysis of official and private documents, aiming to analyze the passage of the above-mentioned historical character through Espírito Santo lands.
Keywords: History of the Espírito Santo; Manoel Tovar; Administration